(untitled) (World Bulletin of Education and Learning, 2025)
Transport development in the contemporary world is subjected to the logic of technical progress and economical expediency. This causes several problems in different spheres of society. In order to amortize the negative by-results of transport development, there is the need for a social theory that would serve as a base for the elaboration of a complex system of criteria that bear the humanist direction of scientific and technical as well as economical thought. Scholars writing in Russian have had some achievements regarding the description and analysis of transport development related to a specific circumstance of selected territories, a concrete kind of vehicle, or a style of transport management. Meanwhile, they face difficulties using terminology and fail to rely on a hard theoretical basis. A review of publications on transport in Russian will identify the weak spots in terminological apparatus for the favor of its improvement. In addition, this may contribute to the international theory of transport.